Maternal immune activation downregulates schizophrenia genes in the foetal mouse brain. Issue 4 (15th November 2021) - Handunnetthi, Lahiru; Saatci, Defne; Hamley, Joseph C; Knight, Julian C
Abstract: Susceptibility to schizophrenia is mediated by genetic and environmental risk factors. Maternal immune activation by infections during pregnancy is hypothesized to be a key environmental risk factor. However, little is known about how maternal immune activation contributes to schizophrenia pathogenesis. In this study, we investigated if maternal immune activation influences the expression of genes associated with schizophrenia in foetal mouse brains. We found that two sets of schizophrenia genes were downregulated more than expected by chance in the foetal mouse brain following maternal immune activation, namely those genes associated with schizophrenia through genome-wide association study (fold change = 1.93, false discovery rate = 4 × 10 −4 ) and downregulated genes in adult schizophrenia brains (fold change = 1.51, false discovery rate = 4 × 10 −10 ). We found that these genes mapped to key biological processes, such as neuronal cell adhesion. We also identified cortical excitatory neurons and inhibitory interneurons as the most vulnerable cell types to the deleterious effects of this interaction. Subsequently, we used gene expression information from herpes simplex virus 1 infection of neuronal precursor cells as orthogonal evidence to support our findings and to demonstrate that schizophrenia-associated cell adhesion genes, PCDHA2, PCDHA3 and PCDHA5, were downregulated following herpes simplex virus 1 infection. Collectively, our results provide novel evidence for a link between genetic and environmental risk factors in schizophrenia pathogenesis. These findings carry important implications for early preventative strategies in schizophrenia. Abstract : Handunnetthi et al. find that schizophrenia genes are downregulated by maternal immune activation mimicking viral infections. These downregulated genes play key roles in neurodevelopmental processes such as neuronal cell adhesion. Overall, these findings provide insight into how genetic and environmental factors may interact in the causal cascade to schizophrenia. Graphical Abstract: